Review of the integrity of a Self Administered Motivational Instrument - Duffy, Tim; McCaig, Marie; McGrandles, Amanda; Rimmer, Russell; Martin, Colin R. (Nurse Education Today, 2013)
BackgroundMotivational interviewing (MI) was developed by Miller and Rollnick as an evidence-based counselling approach for use in supporting people with alcohol problems. Over the years the principles and spirit of MI have been reviewed and fine-tuned and the approach has been embraced by practitioners worldwide and across fields.Since 2001 a number of instruments have been designed to evaluate the fidelity of MI practice. For the purposes of this study, one such instrument is used to assess a self-administered motivational instrument, known as the SAMI, which takes the interviewer role.ObjectivesThe SAMI is evaluated against the MITI 3.1.1, which is designed to assess the extent to which MI interventions perform on five global dimensions. These are evocation, collaboration, autonomy/support, direction and empathy.DesignThe SAMI was assembled based on the principles and spirit of MI, problem solving and goal-setting. The targeted behaviour changes were student learning styles and approaches to study.SettingThe SAMI was distributed, completed and submitted electronically via the university virtual learning environment.ParticipantsThirty three mature students of a university which delivered online nursing programme were invited to complete the SAMI. Of these, 25 submitted completed transcripts.MethodsTranscripts of a sample of six completed SAMIs were assessed by a group of teachers and researchers with experience in the use and evaluation of MI, using five-point Likert scales to assess the SAMI on the five dimensions.ResultsOverall, an average score exceeding 4.5 was attained across the five dimensions. Conventionally, such a score is recognised as competency in MI. However, on one dimension (empathy), the rating was three.ConclusionsThis current research confirms that global principles have been observed in the online delivery of MI using the SAMI to probe approaches to study.